Financial crisis and information gaps: Comments on a proposal by Otmar Issing and Jan Pieter Krahnen - Bernd Braasch (Intereconomics, 2009)
Against the background of the present financial crisis Otmar Issing and Jan Krahnen, members of the expert commission advising the German government on issues relating to financial crisis prevention, have suggested the creation of a global risk map to be enhanced by a global credit register. The following article comments and elaborates on this proposal and its practical implementation.
Keywords: 330